1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein‐Phosphorylation Events in the Anoxia Signal‐Transduction Pathway Leading to the Inhibition of Total Protein Synthesis in Isolated Hepatocytes

Abstract: Incubation of isolated hepatocytes under N,/COZ (no 0,) produced a rapid and strong inhibition of overall polypeptide biosynthesis, which was neither related to cell death nor to the appearance of specific stress proteins. Treatment of the cells with the tyrosine-kinase inhibitor genistein or with the serine/ threonine-protein-kinaqe inhibitor H7 did not modify the impairment of protein synthesis induced by oxygen deprivation, indicating that such signal-transduction pathways are probably not involved in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Studies on hepatocytes have shown that protein synthesis is largely inhibited in response to hypoxia. 16 Buttgereit and Brand 17 demonstrated that, in fact, the ATP consuming processes are arranged in a hierarchy, with protein synthesis and RNA/DNA synthesis being the first to be inhibited as energy becomes limiting and with Na ϩ /K ϩ pumping and Ca 2ϩ cycling taking the greatest priority. This phenomenon, known as oxygen conformance, involves precise regulatory mechanisms notably at the level of translation initiation.…”
Section: Adaptation To Hypoxiamentioning
confidence: 99%
“…Studies on hepatocytes have shown that protein synthesis is largely inhibited in response to hypoxia. 16 Buttgereit and Brand 17 demonstrated that, in fact, the ATP consuming processes are arranged in a hierarchy, with protein synthesis and RNA/DNA synthesis being the first to be inhibited as energy becomes limiting and with Na ϩ /K ϩ pumping and Ca 2ϩ cycling taking the greatest priority. This phenomenon, known as oxygen conformance, involves precise regulatory mechanisms notably at the level of translation initiation.…”
Section: Adaptation To Hypoxiamentioning
confidence: 99%
“…43,54,55 For example, anoxia activates AMPK and this leads to the phosphorylation of eEF2 and inhibition of translation elongation (Fig. 2).…”
Section: Hypoxia and Translational Controlmentioning
confidence: 99%
“…This mechanism and the sequence of the phosphorylation site in eIF2α are conserved between yeast and man. An increase in the extent of eIF2α phosphorylation occurs concomitantly with a downregulation of the rate of protein synthesis in normal tissues responding to a diverse array of stresses, including heat shock (Hu et al, 1993), amino acid deprivation (Kimball et al, 1991), reperfusion following ischemia (Martin de la Vega et al, 2001) and anoxia (Tinton et al, 1997).…”
mentioning
confidence: 99%